Analisis Minimisasi Biaya Distribusi Beras Dengan Menggunakan LINEAR PROGRAMMING Oleh Perum Bulog Divisi Riau dan Kepri - Khairul Fahmi; Ermi Tety; Ahmad Rifai (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
In an effort to strengthen food security in Indonesia, the government set up a separate body to deal with the problem of food that Bulog. Bulog rice procurement allocation include Beras Miskin (Raskin), Cadangan Beras Pemerintah (CBP) and Operasi Pasar Murni (OPM). To meet the needs in the province of Riau and Riau Islands province, Bulog Regional Division Riau and Riau Islands should make the process of optimal distribution of rice at a low cost. Optimization of warehouse inventory and minimize distribution costs can be done by applying a Linear Programming optimization method is a method of transportation. From the results of the use of QM For Windows applications by using two models formulation obtained distribution costs are minimal formulation of model 2 is the model minimization by maximizing the capacity of the warehouse, with a total cost of Rp.1.135.736.404, where the cost is much less than formulation of the model 1 is a model minimization by considering the sheer number of needs the warehouse at a cost of Rp.1.240.804.404. Keywords: Cost Minimisation, Distribution, Linear Programming.